Filarial nematodes with zoonotic potential in ring-tailed coatis (Nasua nasua Linnaeus, 1766, Carnivora: Procyonidae) and domestic dogs from Iguaçu National Park, Brazil - Moraes, Marcela Figuerêdo Duarte [UNESP]; da Silva, Marina Xavier; Magalhães-Matos, Paulo Cesar; de Albuquerque, Ana Cláudia Alexandre [UNESP]; Tebaldi, José Hairton [UNESP]; Mathias, Luis Antônio [UNESP]; Lux Hoppe, Estevam G. [UNESP] (Elsevier, 2017)
Iguaçu National Park, which contains the largest remnant of Atlantic Forest in southern Brazil and Iguaçu Falls as one of its main visiting points, is a year-round attraction for thousands of domestic and international tourists. Ring-tailed coatis are generalist, opportunistic carnivores that benefit from human association. These animals are the most abundant carnivores in this park, where they come into close contact with tourists and the resident population around the park. Moreover, as the park is surrounded by human dwellings, free roaming domestic dogs are frequently present, favoring the exchange of pathogens with wild animals. Wild carnivores are known to be infected with several pathogens, from viruses to arthropods, some of them passed on by domestic carnivores. Among the nematodes that infect wild carnivores, those of the Onchocercidae family are of concern due to their zoonotic potential. The objective of this research was to assess the prevalence of filarial nematodes in coatis and dogs in Iguaçu National Park, as well as the potential impact of infection on host health and body condition. To this end, 75 coatis and 50 adult dogs were captured in the aforementioned area. Seven species of filarioids, Dirofilaria immitis, Dirofilaria repens, Acanthocheilonema reconditum, Brugia sp., Mansonella sp. and two undetermined species, confirmed by histochemical tests, were diagnosed in the area. Knott's concentration test in coatis and dogs showed a prevalence of 81.6% and 16.0%, respectively. Seven microfilarial morphotypes were diagnosed in the coatis and two morphotypes were found in the dogs. A specific immunoassay test for Dirofilaria immitis revealed the presence of D. immitis infection in 1.33% of the coatis and 22% of the domestic dogs. The parasitic infection had negligible effects on the body condition of both dog and coati hosts, but an increase was found in eosinophil counts in coatis with filarial infection, as well as decreases in hematocrit and hemoglobin in the infected domestic dogs. These findings represent new locality and host records for all the filarioids diagnosed in the area of this study, with some of the diagnosed parasites, given their zoonotic potential, representing a health risk for park visitors and the local population.
Keywords: Atlantic rainforest; Filariasis; Histochemistry; Host-parasite interactions; Knott's test